O efeito da aclimatização no reconhecimento de sentenças no silêncio e no ruído: avaliação sem as próteses auditivas - Santos, Sinéia Neujahr dos (2009)
OBJECTIVE: To determine the effect of acclimatization in the sentences recognition in quiet and in noise, in new users of hearing aids evaluated before and after the acclimatization period, without the use of them. METHODS: The study was conducted at the at the Language and Hearing Sciences Attendance Service of Universidade Federal de Santa Maria (UFSM) and included 40 individuals, aged between 28 and 78 years old with sensorineural hearing loss of mild to moderate. They were starting the process of selection and adaptation of hearing aids. The tests were conducted in three sessions, before the adaptation of hearing aids, fourteen days and three months later. It was applied to Portuguese Sentences Lists test (COSTA, 1997), in free field, and obtained the sentences recognition thresholds in quiet (SRTQ) and in noise (SRTN), this fixed at 65 dB A and the results expressed through the signal/noise ratios. Also searched the percentual indexes of sentences recognition in quiet (PISRQ) and in noise, both in fixed intensity of 65 dB A. RESULTS: The average values for the SRTQ in the 1st, 2nd and 3rd sessions were, respectively, 54.43, 51.71 and 52.22 dB A. The averages of the signal/noise ratios to the 1st, 2nd and 3rd sessions were 1.67, 0.30 and -0.03 dB A. While comparing the results obtained between sessions, there was a statistically significant difference between the 1st and 2nd, and between the 1st and 3rd session for the measures obtained in quiet and in noise. For the indices, were found average values for the PISRQ in the 1st, 2nd and 3rd sessions were, respectively, 65%; 72% e 83% dB A. The averages of the PISRN to the 1st, 2nd and 3rd sessions were 51%; 58% e 59% dB A. While comparing the results obtained between sessions, there was a statistically significant difference, for PISRQ, between the 1st and 3rd e and between the 2nd and 3rd session and, for PISRN, between the 1st and 2nd e and between the 1st and 3rd session. CONCLUSIONS: The subjects gradually improved their performance over the use of hearing aids, even evaluated without them and this improvement may be related to the effect of acclimatization.